Warm Water Pool System Simulation: Design and Manufacture - Ida Bagus Gde Widiantara; I Wayan Suastawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Human development and national competitivenes is one of the flagship programs from The Indonesian Government. Bali as one of the best tourist destination in the world is required to have an international standard tourism infrastructure. A swimming pool in a tourism accomodation is a standard facility in a tourist infrastructure. There are several types of swimming pools i.e. public swimming pools and private pools. During its development and demand, private pools develop into swimming pools with additional facilities such as warm water, which is often called a jacuzzi. Another additional facility is added pressure to the water in completing massage, fragrance and foam. The swimming pool is one of facilitity designed to hold water to allow swimming or other recreational activities. Pools can be built in the ground or on the ground as a free construction or as a part of structure and also with a common feature or a free style design. In-ground pools are the most common pools made and constructed from materials such as concrete, natural stone, metal, plastic, or fiberglass. To support comfort and satisfaction when using the swimming pool, the adequate water level in the swimming pool will be maintained by system with several supporting devices such as pumps, dirt filters and maintained at a certain level. Other things that support water quality include temperature, water turbidity, color, odor, pH, chlorine content etc.